DEVELOPMENT OF FRUIT PRODUCTION AND PROCESSING IN THE REPUBLIC OF SERBIA - Lukač Bulatović, Mirjana; Rajić, Zoran; Đoković, Jelena (Economics of Agriculture, 2013)
Although Serbia is characterized by favourable natural conditions for growing most of the continental fruit species, the full potential of their exploitation has not been reached yet. The main indicators of this underutilisation are values of main parameters of fruit production during longer periods of time. Due to its mostly extensive feature, the fruit production in Serbia has been ground to a halt for a considerable period of time, and has even shown the signs of reduction. In the period from 1981 to 2011, orchard areas in Serbia covered 252,364 ha on average, with the annual reduction rate of -0.40%. During the analysed period (2001-2010), the highest production volume of processed fruit products (semi-processed and finished products) was recorded in fruit juices (155,012 t) and frozen fruits (24,602 t). Fruit juices and frozen fruits account for 93% of the total processed fruit products in Serbia. The processed fruit production during the analysed period increased at the average annual rate of change of 14.82%.